Costs of sleeping in: circadian rhythms influence cuckoldry risk in a songbird. (4th June 2015) - Greives, Timothy J.; Kingma, Sjouke A.; Kranstauber, Bart; Mortega, Kim; Wikelski, Martin; van Oers, Kees; Mateman, A. Christa; Ferguson, Glen A.; Beltrami, Giulia; Hau, Michaela
Summary: Circadian (i.e. daily) regulation of behaviours is thought to provide fitness benefits to organisms by enabling them to anticipate diel changes in the environment, such as sunrise. A common behaviour among socially monogamous songbirds that usually takes place in the early mornings is extra‐pair mating, that is copulating with partners outside of the social pair bond. Thus, variation in when individuals begin their daily activity may influence their reproductive success; early risers may be better able to gain copulations and guard their partners, thus minimizing their risk of being cuckolded compared with late risers. Sexual selection may thus play an important role in shaping circadian behaviours, but this assumption has yet to be tested in free‐living animals. Here, we experimentally weakened endogenous circadian rhythmicity, and thus, anticipation of dawn in male great tits ( Parus major ) in the wild through the subcutaneous administration of implants filled with melatonin shortly before egg‐laying began in this population. Melatonin is a hormone released during the dark phase at night and is one important cue animals use to entrain their circadian clock. Experimental individuals delayed the onset of daily activity compared with controls and were more likely to be cuckolded compared with control males. Manipulation did not alter other behavioural traits observed; no difference between treatments was observed in activity levels during the day or in the end time of daily activity. These results strongly support the assumption that selection, particularly sexual selection, shapes the circadian phenotypes of wild vertebrates which enable anticipation of important and predictive diel changes in an individual's biotic and abiotic environment. Abstract : Lay Summary